Action on Pilocarpine on the Guinea-Pig Tracheal Chain. (Journal of Science and Technology, 2016)
The muscarinic drugs carbachol and pilocarpine were used as tone-inducing  agents on the guinea-pig tracheal chain preparation in an attempt to evaluate bronchodilator activity on the tissue. Whereas carbachol produced contraction of the tissue in all the doses used, pilocarpine had an unpredictable action in that it caused contraction of some 'tissues while producing an initial relaxation of others in the dose range used. Theβ-adrenoceptor drugs isoprenaline and cimaterol were found to be more potent in-relaxing pilocarpine than carbachol-induced tone.